A Literature Review: Entrepreneurial Leadership in Indonesia - Chafifa Aulia Keleng; Andi Indriani Ibrahim; Syahbudin Adam; Nadya Mulia Supu; Nina Pamoras; Fadilah; Sri Ferni Rahmawati (Universitas Muhammadiyah Palu, 2025)
Entrepreneurial leadership is a leadership style that combines managerial, innovative, and risk-taking abilities to create added value within an organization. In Indonesia, this concept is increasingly relevant across various sectors, including education, Islamic boarding schools (pesantren), SMEs, religious organizations, and corporate environments. Entrepreneurial leadership plays a vital role in navigating the challenges of digital transformation and the creative economy era. This literature review aims to analyze the trends, models, and impact of entrepreneurial leadership in Indonesia based on recent research. This study employs a literature review method by examining 20 national scholarly articles published between 2019 and 2025. Data were obtained from open-access journals, books, and relevant research reports. The findings indicate that entrepreneurial leadership significantly enhances organizational performance, fosters pesantren economic independence, strengthens entrepreneurial orientation in SMEs, and encourages innovation in educational and religious institutions. Entrepreneurial leadership is essential for improving competitiveness and sustainability in Indonesian organizations, although it still faces challenges in human resource development, organizational culture, and policy support.